2010
DOI: 10.1093/toxsci/kfq304
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Polycyclic Aromatic Hydrocarbon Exposure Leads to Behavioral Deficits and Downregulation of Receptor Tyrosine Kinase, MET

Abstract: Gene by environment interactions (G × E) are thought to underlie neurodevelopmental disorder, etiology, neurodegenerative disorders, including the multiple forms of autism spectrum disorder. However, there is limited biological information, indicating an interaction between specific genes and environmental components. The present study focuses on a major component of airborne pollutants, polycyclic aromatic hydrocarbons (PAHs), such as benzo(a)pyrene [B(a)P], which negatively impacts cognitive development in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 48 publications
6
31
0
Order By: Relevance
“…35,36 Animal studies of PAH-induced neurotoxicity have focused primarily on brain gray matter, but our findings suggest that they should investigate PAH effects on white matter as well.…”
Section: Discussionmentioning
confidence: 90%
“…35,36 Animal studies of PAH-induced neurotoxicity have focused primarily on brain gray matter, but our findings suggest that they should investigate PAH effects on white matter as well.…”
Section: Discussionmentioning
confidence: 90%
“…Exposed rats exhibit reductions in evoked potential in cortex [73] and decreased LTP in dentate gyrus of the hippocampus relative to control rats [20]. Impaired learning and memory (adverse outcome): Several studies have shown impaired learning and memory in rodents exposed to BaP in utero and during adulthood [12,[50][51][52]77,103]. Table 9 provides a summary of the evidence for the proposed KEs in rats and mice.…”
Section: Key Eventsmentioning
confidence: 99%
“…1 In previous independent studies, we have identified (1) increased autism spectrum disorder risk among children exposed to high levels of local near-roadway traffic-related air pollution and regional particulate matter near the time of birth 2,3 ; (2) increased autism spectrum disorder risk among children with the C allele of the MET gene promoter variant rs1858830, 4,5 which is associated with decreased expression of MET protein in brain 6 and immune system 7 ; and (3) decreased MET protein expression in brain and altered behavior in offspring of mouse dams exposed during pregnancy to the polycyclic aromatic hydrocarbon benzo(a)pyrene (a component of traffic-related air pollution and particulate matter). 8 Based on these independent autism spectrum disorder associations and the biological link between benzo(a)pyrene and MET , we hypothesized that a gene-environment interaction contributes to autism spectrum disorder risk.…”
mentioning
confidence: 99%